Dynamic-IMD (D-IMD): Introducing activity spaces to deprivation measurement in London, Birmingham and Liverpool. (August 2022) - Comber, Sam; Park, Souneil; Arribas-Bel, Daniel
Abstract: Indicators of deprivation intersect a variety of disciplinary contexts. In this article, we build a multi-space measure of deprivation by introducing urban mobilities derived from location footprints of nearly three million mobile phone users. Traditionally, experiences of deprivation have been estimated through a lens fixed to residential spaces, which overlooks the likelihood individuals experience deprivation beyond that implied by where they live. By quantifying how exposure to deprivation varies by human movement patterns across three English cities, we construct a Dynamic Index of Multiple Deprivation (D-IMD). Analysis of this measure highlights how deprivation exposure converges to a more homogenous middle ground, which implies the deprivation gap lessens as individuals across the socio-economic spectrum coalesce in spaces that exhibit similar environmental conditions. Using a hypothetical example, our D-IMD measure identifies 185 neighbourhoods that would enter England's eligibility criteria for funding opportunity intended to alleviate socio-economic inequality and hardship. These practical implications are extensible to international contexts that mobilise deprivation indices in similar ways to English institutions. Highlights: Deprivation measurement is typically explored from a static, fixed-location perspective Introduce activity spaces estimated from location footprints of nearly three million mobile users to deprivation measurement We find convergence in deprivation experiences across socioeconomic spectrum when introducing urban mobilities Relationships are also observed between D-IMD measure and the underlying urban landscape Measure finds 185 neighbourhoods enter England's elibility criteria for funding opportunity designed to alleviate hardship